Pengaruh Good Corporate Governance (GCG) dan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Mochamad Sulthan Firdaus; Tantina Haryati (Journal of Management and Bussines (JOMB), 2024)
This research aims to evaluate the influence of Good Corporate Governance (GCG) and CSR on Company Value, with Profitability as a moderating variable. Quantitative methodology is used with data on shares of state-owned companies on the Indonesian Stock Exchange in the 2017-2021 period. Research participants involved shares of state-owned companies, and data was collected from the Indonesia Stock Exchange website, and analyzed using smart PLS4 software. The research results show that profitability has a moderating effect on managerial ownership, independent board of commissioners, and CSR on company value. The conclusion is that the management of BUMN subsidiary companies can take further steps to maximize the use of managerial ownership, strengthen the role of the independent board of commissioners, and develop corporate social responsibility (CSR). This becomes more important in facing rapid developments in science, information technology and increasingly fierce global business competition. This research is original with a focus on the correlation between GCG, CSR and company value, considering profitability as a moderating variable. Keywords: CSR, GCG, Company Value, SEM